1998
DOI: 10.1017/s0305000998003547
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes and variability in the early lexicon: a study of French children's naturalistic productions

Abstract: This paper investigates developmental changes, as well as inter-linguistic and inter-individual variations, in the expansion and composition of French children's early lexicons. Two studies were conducted using children's naturalistic productions: a longitudinal study of one child between 1;2 and 2;6, and a cross-sectional study of two groups (12 children each) aged 1;8 and 2;6. Analyses indicate that lexical productivity (measured in types, tokens, and new words) strongly increased with age, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
21

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 0 publications
6
34
0
21
Order By: Relevance
“…Evidence from naturalistic recordings A longitudinal study of one French child and a cross-sectional study of two age groups of French children (1 ; 8 and 2;6, 12 children each) showed a higher proportion of nouns than verbs (Bassano, Maillochon & Eme, 1998 ;Bassano, 2000). However, the first French verbs in the corpus occurred as early as the first nouns.…”
Section: A R E N O U N S M O R E F R E Q U E N T T H a N V E R B S I mentioning
confidence: 99%
“…Evidence from naturalistic recordings A longitudinal study of one French child and a cross-sectional study of two age groups of French children (1 ; 8 and 2;6, 12 children each) showed a higher proportion of nouns than verbs (Bassano, Maillochon & Eme, 1998 ;Bassano, 2000). However, the first French verbs in the corpus occurred as early as the first nouns.…”
Section: A R E N O U N S M O R E F R E Q U E N T T H a N V E R B S I mentioning
confidence: 99%
“…ABFW´s Vocabulary Test was used to assess the lexical competence of the subject, as from five years of age children´s vocabulary quantitatively similar to that of an ordinary adult 9 . The assessments were categorized as normal or altered.…”
Section: Methodsmentioning
confidence: 99%
“…Ce constat est basée sur des données naturelles spontanées (Bassano, 2000 ;Bassano et al, 1998 ;Parisse et Lenormand, 2000) et des compte-rendus parentaux (Kern, 2007 ;Kern & Gayraud, 2010). Parisse et Lenormand (2000) ont enregistré les jeux symboliques de 27 enfants francophones de 2 ans.…”
Section: Comparaison Français-turcunclassified
“…Ils rapportent un nombre plus important de types de noms que de types de verbes : 29% de noms différents sont produits dans les énoncés à un seul mot et 44% dans les énoncés de plus d'un mot contre 18% et 22% seulement de verbes. Dans une étude longitudinale portant sur une enfant francophone entre 14 et 30 mois ainsi que dans une étude transversale de 12 enfants observés à 12 et à 30 mois, Bassano et al (1998) Les sujets ont été filmés au domicile des parents en interaction avec leur mère lors de deux situations différentes : la lecture partagée d'un album d'images sans texte et un jeu avec une maison de poupées. Chaque situation dure 10 minutes.…”
Section: Comparaison Français-turcunclassified